Sufi Masters and the Creation of Saintly Spheres in Medieval Syria. - Ephrat, Daphna. (Medieval Islamicate World Series, 2021)
This study explores the creation of saintly spheres in medieval Syrian landscapes surrounding Sufi masters and friends of God.